2015
DOI: 10.1002/jgm.2831
|View full text |Cite
|
Sign up to set email alerts
|

RedesignedEscherichia colicytosine deaminase: a new facet of suicide gene therapy

Abstract: We report a novel bacterial CD mutant that provided a superior alternate to the wtCD suicide gene. The F186W mutant required a much lower dose of 5-FC to reach its IC50 , thus minimizing the systemic side effects of large doses of 5-FC as required for wtCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Stable transfection of Cx43 was performed as described previously in ref. 20 . The overexpression of Cx43 was assessed by semi-quantitative PCR and quantitative real-time PCR (qPCR; primer sequences provided in supplementary info).…”
Section: Methodsmentioning
confidence: 99%
“…Stable transfection of Cx43 was performed as described previously in ref. 20 . The overexpression of Cx43 was assessed by semi-quantitative PCR and quantitative real-time PCR (qPCR; primer sequences provided in supplementary info).…”
Section: Methodsmentioning
confidence: 99%
“…Although these approaches have looked promising in some pre-clinical models, the low efficiency of bacterial CD to convert 5-FC into 5-FU limited the overall therapeutic response. Recently, Ghosh et al have mutated CD to increase its affinity to 5-FC and reduce the amount of 5-FC required as prodrug [42–44]. …”
Section: Evolution Of Safety Switchesmentioning
confidence: 99%
“…One set of switches targets surface molecules (CD20, EGFR) [3237], while a second uses a transgenic enzyme to activate a cytotoxic pro-drug (HSV-thymidine kinase gene + GCV or cytosine deaminase + 5FC) [3844]. Engineering therapeutic T cells with a peptide-specific antibody-based switch is another strategy to control the activation and expansion of these cells [45].…”
Section: Introductionmentioning
confidence: 99%
“…Also, cytosine deaminase has a poor binding affinity towards 5-FC compared to the natural substrate cytosine, unless a mutated form of the enzyme is used. 22 (iii) Selective elimination of PSC by an oleate synthesis inhibitor discovered in a high-throughput screen 23 ; however these compounds have so far been given only pretransplantation and most likely act only on cells in the pluripotency stage and not on proliferating neuroprecursors.(iv) A recent study has suggested that irradiation of transplanted cells could be an alternative to a suicide gene technology to achieve elimination of proliferating cells. Given the potential toxicity of CNS irradiation, we do not think that this approach is the most promising for future application in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cytosine deaminase has a poor binding affinity towards 5-FC compared to the natural substrate cytosine, unless a mutated form of the enzyme is used. 22 …”
Section: Discussionmentioning
confidence: 99%